High energy ultrafast laser at 2 μm using dispersion engineered Thulium-doped fiber - Chen, Yuhao (2021)
We report on demonstration of high energy pulse laser at 2 μm by employing a normal dispersion fiber attained by a waveguide dispersion engineering. The normal dispersion fiber has a W-type refractive index profile, with a Thulium(Tm)-doped core. In contrast to a strong anomalous dispersion at 2 μm in a step-index fiber, the design allows strong waveguide dispersion that can generate normal dispersion at the Tm emission band. Mode area scalability of this fiber is discussed under the normal dispersion requirement. The Tm-doped fiber (TDF) is deployed in a ring cavity to produce mode-locked pulses near 2 μm. Subsequently, the pulse is amplified with more than 27 dB gain through the normal dispersion TDF. The output pulse energy reaches up to ∼525 nJ at 1852 nm without pulse breaking due to the engineered dispersion. The achieved pulse energy is record high for all-fiber configuration near 2 μm, to our knowledge.